2020
DOI: 10.3390/v12060665
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle Activation of Latent HIV-1 Is Driven by EV-Associated c-Src and Cellular SRC-1 via the PI3K/AKT/mTOR Pathway

Abstract: HIV-1 is a global health crisis that has infected more than 37 million people. Latent reservoirs throughout the body are a major hurdle when it comes to eradicating the virus. In our previous study, we found that exosomes, a type of extracellular vesicle (EV), from uninfected cells activate the transcription of HIV-1 in latent infected cells, regardless of combination antiretroviral therapy (cART). In this study, we investigated the specific mechanism behind the EV activation of latent HIV-1. We found that pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…It has been shown that HIV-1 infection promotes the release of EVs containing viral molecules and host components from the infected cells (e.g., monocytes, macrophages, dendritic cells, and T cells) [ 87 , 97 , 98 ], pointing to the essential role of EVs in viral spread. For instance, EVs derived from an uninfected T-cell line (i.e., CEM cells) were shown to reverse latency in HIV-1-infected cells in a process mediated by EV-associated to a non-receptor tyrosine kinase (c-Src) [ 99 , 100 ]. This kinase is involved in NF-kB signaling pathways, involved in cellular proliferation, differentiation, motility, and angiogenesis.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…It has been shown that HIV-1 infection promotes the release of EVs containing viral molecules and host components from the infected cells (e.g., monocytes, macrophages, dendritic cells, and T cells) [ 87 , 97 , 98 ], pointing to the essential role of EVs in viral spread. For instance, EVs derived from an uninfected T-cell line (i.e., CEM cells) were shown to reverse latency in HIV-1-infected cells in a process mediated by EV-associated to a non-receptor tyrosine kinase (c-Src) [ 99 , 100 ]. This kinase is involved in NF-kB signaling pathways, involved in cellular proliferation, differentiation, motility, and angiogenesis.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…As described previously, TAR RNA is essential for HIV Tat and protein kinase(s) RNA-activated (PKR) binding, however, the TAR miRNA binds to TLR7/TLR8, but not PKR [ 167 ]. Coculturing exosomal vesicles containing Tat, TAR RNA, TAR miRNA, and a newly found TAR-gag RNA induced IL-6, TNFβ, NF-κB pathways, cytokine production, and overall cellular activation of the recipient/neighbor cells, ultimately causing latency reversion [ 167 , 168 , 170 , 171 ]. These TAR RNA-containing exosomes also induced cancer-cell proliferation and progression by affecting expression of proto-oncogenes and TLR3 inducible genes, which reduced apoptosis in neighboring latency-reversing cells by lowering Bim and CDK9 protein levels [ 166 , 172 ].…”
Section: Hiv Latency and Potential Agents For Reversalmentioning
confidence: 99%
“…EVs facilitate viral transmission HSV-1 (Bello-Morales and López-Guerrero, 2020), KSHV (Chen et al, 2020)., NDV (Zhou C. et al, 2019), PRRSV (Wang et al, 2017), enterovirus 71 (Gu et al, 2020), HCV (Bukong et al, 2014), HIV (Kadiu et al, 2012), SFTS (Silvas et al, 2016) Viral RNAs/proteins inside EVs Coronavirus (Maeda et al, 1999), EBV (Keryer-Bibens et al, 2006), HCV (Kouwaki et al, 2017)., HTLV-1, (Jaworski et al, 2014), RVFV (Ahsan et al, 2016), ZIKV (Zhou W. et al, 2019;Martıńez-Rojas et al, 2020) Infectious virus-like particles/cloaked virions inside EVs DENV (Reyes-Ruiz et al, 2019), enterovirus 71 (Gu et al, 2020), HCV (Bartosch et al, 2003;Timpe et al, 2008) Transfer of infective RNA through EVs withouth complete viral particles HCV (Longatti et al, 2015), FMDV (Zhang et al, 2019), EVs turn cells more permissive to infection, membrane/receptor modulation HIV (Arenaccio et al, 2014;Dubrovsky et al, 2020), Rhinovirus (Miura, 2019) Host molecules in EVs facilitate viral stability and replication in recipient cells HBV , HCV (Bukong et al, 2014;Altan-Bonnet, 2016), HIV (Arenaccio et al, 2014;Ranjit et al, 2020) Amplification of EV production ZIKV (Zhou W. et al, 2019) EVs from uninfected cells can activate latent viruses HIV (Barclay et al, 2020) EVS RELATED TO IMMUNE RESPONSES…”
Section: Mechanism Virusmentioning
confidence: 99%
“…Mediate chemoresistance HBV (Liu D. et al, 2019) Mediate autoimmunity/transplant rejection respiratory viruses (Gunasekaran et al, 2020). EVs involved in viral latency/persistant infections HIV (Olivetta et al, 2019;Barclay et al, 2020), HCV (Ashraf Malik et al, 2019), Thrombosis induction SARS CoV-2 (Inal, 2020a), Nomura et al, 2020 induced signaling as an immune evasion strategy (Florentin et al, 2012). A recently explored area gaining attention involves the transfer of ISGs through EVs.…”
Section: Mechanism Virusmentioning
confidence: 99%
See 1 more Smart Citation